The Caribbean Space in Rastro de sal by Arabella Salaverry - Alpízar, Diana Martínez (2023)
The present paper analyses the setting up of the Caribbean space in the novel Rastro de sal by the Costa Rican writer Arabella Salaverry. This space is approached from two different perspectives: the first one is linked with the general representation of the Caribbean space. This analysis focuses on three relations in specific: connectivity/isolation; nature/culture; center/periphery. The second perspective is interested in the domestic space and its interactions with the female characters, based on the following relations: liberty/ imprisonment; interior/exterior. It concludes that in Rastro de sal the Caribbean space is showed as contradictory, dynamic, and unequal.